Safety design planning of ground grid for outdoor substations in MEA's power distribution system - Phayomhom A. (2014)
This paper analyzes the performance of a ground-ing system made of copper conductors and signicantly influenced by soil resistivity. The grounding performance is evaluated in terms of ground potential rise (GPR), touch voltage and step voltage caused by a short circuit that generates a flow of large cur-rents in the aboveground structures and grounding system and dissipates in the soil. These currents may cause damage to substation equipment and may be dangerous to personnel working nearby. Safety design planning for step and touch voltages for the existing fault level and future fault levels are extensively investigated for utility applications where personnel hazards may exist. Modelling and simulation is carried out on the Current Distribution Electro-magnetic interference Grounding and Soil structure (CDEGS) program. The safety design planning is illustrated by a practical case of ground grid design for the 69/12-24 kV, outdoor-type Bangkrachao sub-station of Metropolitan Electricity Authority (MEA) with economic analysis. An effective solution to improve the performance of the substation grounding is also suggested.